Defining Uremic Arterial Functional Abnormalities in Patients Recently Started on Haemodialysis: Combined In Vivo and Ex Vivo Assessment - Abushufa, Adil M. (PLoS One, 2014)
Endothelial dysfunction is a key initiating event in vascular disease in chronic kidney disease (CKD) patients and haemodialysis (HD) patients exhibit significant vascular abnormalities. To understand this further, we examined how ex vivo intrinsic function in isolated arteries correlates with in vivo assessments of cardiovascular status in HD patients. Abdominal fat biopsies were obtained from 11 HD patients and 26 non-uremic controls. Subcutaneous arteries were dissected and mounted on a wire myograph, and cumulative concentration-response curves to noradrenalin, endothelin-1, a thromboxane A(2) agonist (U46619), angiotensin II, vasopressin, bradykinin (BK), acetylcholine (ACh) and sodium nitroprusside (SNP) were constructed. Pulse wave velocity and blood pressure were measured in HD patients. Enhanced (P<0.05−0.0001) maximal contractile responses (R(max)) to all spasmogens (particularly vasopressin) were observed in arteries from HD patients compared to controls, and this effect was more pronounced in arteries with an internal diameter>600 µm. The potency (pEC(50)) of U46619 (P<0.01) and vasopressin (P<0.001) was also increased in arteries>600 µm of HD patients. The maximal relaxant response to the endothelium-dependent dilators ACh and BK were lower in HD patients (P<0.01-P<0.0001) (worse for ACh than BK); however the endothelium-independent dilator SNP was similar in both groups. PWV was significantly correlated with the vasoconstrictor response to vasopressin (P = 0.042) in HD patients. HD patients are primed for hypertension and end organ demand ischaemia by a highly sensitised pressor response. The failure of arterial relaxation is mediated by endothelial dysfunction. Intrinsic vascular abnormalities may be important in sensitising HD patients to recurrent cumulative ischaemic end organ injury.